Improved photon-number squeezing in light-emitting diodes - Wolfl, F; Schucan, G; Fox, A; Ryan, J (1998)
We report photon-number squeezing measurements on high-efficiency double heterojunction AlGaAs infrared light-emitting diodes. The overall current-to-current efficiency was 0.25 at room temperature and 0.40 at 77 K, resulting in a noise reduction below the Standard Quantum Limit of 1.1 dB and 2.0 dB, respectively. In addition, photocurrent correlation experiments were carried out with 2 or 3 LEDs in series, revealing a normalized correlation coefficient of 0.25 at room temperature and 0.40 at 77 K.